Did health professionals accept the COVID-19 vaccination at the initial period of its introduction? - Singkun, Awirut; Maneeprom, Natthawadee; Patiwikraiwong, Piriya; Booraka, Hanifah (Edelweiss Applied Science and Technology, 2025)
Health professionals are essential informants to encourage people to receive the COVID-19 vaccination for herd immunity, ensuring that all people in the community are protected. This study aimed to assess the COVID-19 vaccination rate and associated factors among health professionals. A cross-sectional study was conducted among 220 health professionals using a rapid online survey in April 2021. The instrument was a self-administered questionnaire tested for content validity and reliability. Demographic data, history of COVID-19 vaccination, and work experiences were presented using frequency and percent. Associated factors were analyzed using binary logistic regression (stepwise LR). A p-value of less than 0.05 was considered statistically significant. The vaccination rate for the COVID-19 vaccination among health professionals was high (83.2%). The associated factors with receiving vaccination were contact with patients and their belongings (aOR 3.9, 95% CI: 1.489–10.468), respected persons (aOR 2.9, 95% CI: 1.114–7.582), and vaccination passports (aOR 2.4, 95% CI: 1.071–5.552). Work characteristics, role models, and approval for vaccination enhanced vaccination acceptance. The benefit of this study could be implemented by increasing self-evaluation of susceptible risk for infection, encouraged by respected persons, and promoting the use of an approval document for vaccination.